Rapid strain-specific identification of two Lactobacillus rhamnosus strains using PCR based on gene family analysis. (July 2021) - Zhang, Chenchen; Yu, Xingtong; Wang, Dai; Gui, Ya; Wang, Chunlei; Li, Qiming; Wang, Jiaqi; Yin, Boxing; Pan, Zhiming; Gu, Ruixia
Abstract: Because the probiotic and growth characteristics of probiotics are strain-specific features, it is crucial to be able to distinguish the probiotic strains from the other strains in the same species. To rapidly identify Lactobacillus rhamnosus at the strain level through PCR, a method for searching for several strain-specific sequences in the genome of a strain was investigated. The whole genomes of L. rhamnosus hsryfm 1301 and L. rhamnosus LV108 were sequenced, and gene family analysis was performed with using L. rhamnosus GG and L. rhamnosus Lc705 as reference strains. Thirty-one and 19 strain-specific open reading frames (ORFs) were found in L. rhamnosus hsryfm 1301 and L. rhamnosus LV108, respectively. Thus, strain-specific primer pairs could be designed in a more rational and controllable manner. Concatenation of several strain-specific primer pairs designed from the strain-specific ORFs (and their adjacent regions) were able to distinguish L. rhamnosus LV108 (primer pairs V2, V4, V5, and V9) or L. rhamnosus hsryfm 1301 (primer pairs H1, H2, H3, and H4) from 12 other L. rhamnosus strains. This strain-specific identification method was determined to be accurate, rapid, economical, reproducible and easy to perform. Highlights: 31 and 19 strain-specific open reading frames were found in hsryfm 1301 and LV108. Fore strain-specific primer pairs were designed for hsryfm 1301 and LV108. Several strain-specific primer pairs made the identification results more reliable. L. rhamnosus strains were identified rapidly at the strain level by PCR. This method is easy to perform, fast, economical, reproducible and accurate.